Program Kemitraan Masyakat Produksi dan Pemasaran Gambir (Uncaria gambir Roxb) - Wedy Nasrul; Dedi Wardianto; Rizalman (Jurnal Pengabdian UntukMu NegeRI, 2020)
Gambir is a specific plant for Indonesia with the central area of ​​West Sumatra Province. Gambir plant processed products are widely used for medicines, cosmetics and dyes. Gambir production has been going on for more than a century in the central villages of West Sumatra Province, but there are still many problems in gambir production that are detrimental to gambir farmers. The problems felt by gambir farmers so far include the fluctuating price of processed gambir products and tend to be cheap. The low price of processed farmers' gambir is because the production process is traditional and mixes with other ingredients so it is not hygienic. Furthermore, the low price of processed gambir products is because they are only sold to collectors in village markets (monopsony market structure). Seeing the above problems, the solution as well as the wishes of the community, first is training and assistance for pure and hygienic gambier processing. Both training and assistance in selling pure products through online media to get more consumers.